Non-homologous end-joining at challenged replication forks: an RNA connection?. Issue 11 (November 2021) - Audoynaud, Charlotte; Vagner, Stéphan; Lambert, Sarah
Abstract : Defective DNA replication, known as 'replication stress', is a source of DNA damage, a hallmark of numerous human diseases, including cancer, developmental defect, neurological disorders, and premature aging. Recent work indicates that non-homologous end-joining (NHEJ) is unexpectedly active during DNA replication to repair replication-born DNA lesions and to safeguard replication fork integrity. However, erroneous NHEJ events are deleterious to genome stability. RNAs are novel regulators of NHEJ activity through their ability to modulate the assembly of repair complexes in trans . At DNA damage sites, RNAs and DNA-embedded ribonucleotides modulate repair efficiency and fidelity. We discuss here how RNAs and associated proteins, including RNA binding proteins, may regulate NHEJ to sustain genome stability during DNA replication. Highlights: Non-homologous end-joining (NHEJ), a double-strand break (DSB) repair pathway, is active during DNA replication, as several NHEJ factors are involved in safeguarding the integrity of newly replicated strands, in repairing replication-induced DSBs, and in restarting replication forks. RNAs at DSBs are instrumental in fueling the DNA damage response and guiding modulation of the fidelity of DNA repair by NHEJ. RNAs are modulators of NHEJ activity acting in trans as scaffolders or in cis to promote RNA-templated DSB repair, thereby regulating the repair pathway choice. Ribonucleotides coexist in the DNA template during unstressed and stressed DNA replication and may influence NHEJ activity at halted replication forks.